Drama sebagai Media Pembelajaran Interaktif untuk Peningkatan Keterampilan Komunikasi dan Pemahaman Budaya Santri di Pondok Pesantren Al Ghozali - Elizabeth Sharon Gumalag; Salsabila Gunawan; Sinta Indri Ningrum (Pengabdian: The National Online Journal of Community Service on Linguistics, Language Teaching, Literature and Culture, 2025)
This community service program was conducted at Al Ghozali Islamic Boarding School to improve students’ communication skills and cultural understanding through the use of drama as an interactive learning medium. The main problem identified was the dominance of conventional teaching methods that limited students’ active participation and self-confidence. The activity employed a participatory and collaborative approach using a Project-Based Learning (PBL) model, including basic drama introduction, dialogue and expression practice, simple drama performances, and reflection sessions. The results indicated increased learning interest and participation, improved self-confidence in communication, better understanding of cultural and social values, as well as enhanced teamwork and creative expression. Therefore, drama can be considered an effective and meaningful alternative learning medium in the pesantren context.